Risk stratification of prostate cancer utilizing apparent diffusion coefficient value and lesion volume on multiparametric MRI. Issue 2 (13th July 2016) - Salami, Simpa S.; Ben‐Levi, Eran; Yaskiv, Oksana; Turkbey, Baris; Villani, Robert; Rastinehad, Ardeshir R.
Abstract : Purpose: To evaluate the performance of apparent diffusion coefficient (ADC) and lesion volume in potentially risk‐stratifying patients with prostate cancer (PCa). Materials and Methods: Men with elevated prostate‐specific antigen or abnormal digital rectal exam underwent a 3T multiparametric magnetic resonance imaging (mpMRI) with endorectal coil. ADC maps were calculated using b values of 0, 500, 1000, and 1500; additional images were obtained with b value of 2000. We prospectively enrolled 312 men with lesions suspicious for cancer (suspicion score 2–5) on mpMRI. MRI/ultrasound fusion‐guided prostate biopsies were performed. Mean ADC of suspicious lesions were correlated against lesion volume, Gleason and D'Amico risk. Results: The cancer detection rate of fusion biopsy per lesion was 45.6% (206/452). Cancerous lesions were larger (median volume: 0.40 vs. 0.30 cm 3 ; P = 0.016). The median ADC (×10 −6 mm 2 /sec) for lesions negative and positive for PCa were 984.5 and 666.5, respectively ( P < 0.0001). The AUC of ADC in predicting PCa was 0.79. Larger lesions were associated with higher risk PCa (Gleason and D'Amico) and lower ADC (all P < 0.0001). Conclusion: The mean ADC of suspicious lesions on mpMRI was inversely correlated, while lesion volume had a direct correlation with PCa detection. Future follow‐up studies are needed to assess longitudinal cancer risks of suspicious mpMRI lesions. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:610–616.